2011
DOI: 10.2135/cropsci2010.07.0440
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Fertility Restoration in A4‐Based, Diverse Maturing Hybrids of Pigeonpea [Cajanus cajan (L.) Millsp.]

Abstract: Recently, a breeding technology for hybrid pigeonpea [Cajanus cajan (L.) Millsp.] based on cytoplasmic‐nuclear male sterility (CMS) and partial natural outcrossing was developed at ICRISAT. The limited number of experimental hybrids tested has shown the presence of a considerable amount of hybrid vigor for seed yield. In the present study, one extra‐early‐ (120 d), two early‐ (150 d), and two late‐maturing (180 d) pigeonpea hybrids were studied to generate information on the genetics of fertility restoration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 7 publications
2
29
0
Order By: Relevance
“…In the first generation (F 1 ) these four leaf types were found recessive in expression against lanceolatus leaf. Recessive gene expression for Obcordifoliate leaf shape was observed by Cruz et al, (1971), Deokar et al, (1972), Chopde et al, (1979) and Saxena et al, (2011). Most of the F 1 plants were found sterile as CMS line; it indicated that the factor for male fertility is located in cytoplasm of four recurrent parents.…”
Section: Hybrid Performancementioning
confidence: 84%
See 2 more Smart Citations
“…In the first generation (F 1 ) these four leaf types were found recessive in expression against lanceolatus leaf. Recessive gene expression for Obcordifoliate leaf shape was observed by Cruz et al, (1971), Deokar et al, (1972), Chopde et al, (1979) and Saxena et al, (2011). Most of the F 1 plants were found sterile as CMS line; it indicated that the factor for male fertility is located in cytoplasm of four recurrent parents.…”
Section: Hybrid Performancementioning
confidence: 84%
“…In addition, different hybrid combinations were made to identify fertility restorer gene and heterotic combiner parents from new leaf type CMS lines. Recently, Saxena et al, (2011) incorporated obcordifoliate leaf shape into A 4 cytoplasm based CMS lines for use as naked eye polymorphic markers. The success of hybrid technology largely dependent on the provision of quality F 1 seeds to the farmers.…”
Section: Issn: 2319-7706 Volume 6 Number 11 (2017) Pp 483-493mentioning
confidence: 99%
See 1 more Smart Citation
“…A perusal of published reports on the genetics of fertility restoration of A 4 CMS system in the medium maturing pigeonpea (Table 2) showed that either one or two dominant genes controlled the fertility restoration with variable gene action. Saxena et al (2011a) reported that the fertility restoration in the early maturing pigeonpea was stable across environments only when both the dominant genes were present together in a single genotype; and the hybrids carrying either of the dominant genes were also fertile but not in all the environments. Dalvi et al( 2008) and Saxena et al(2014a) examined over 2000 testers from pigeonpea germplasm across the maturities and reported that, in compaison to early maturing germplasm, the fertility restoring genes were more frequent in the medium maturing pigeonpea germplasm.…”
Section: Resultsmentioning
confidence: 99%
“…In most crops one or two dominant fertility restorer genes have been reported to control the pollen fertility (Kaul 1988 ). Saxena et al ( 2011 ) reported that in pigeon pea two dominant genes were responsible for fertility restoration of A 4 cytoplasm. However, the hybrids with a single dominant gene were also fertile, but they produced less quantity of pollen and also showed a lot of instability with respect to fertility restoration in diverse environments.…”
Section: Fertility Restoration Of Malesterile Germplasmmentioning
confidence: 99%